Search for an exotic decay of the Higgs boson to a pair of light pseudoscalars in the final state with two muons and two b quarks in pp collisions at 13 TeV - Sirunyan, A. M. (2019)
A search for exotic decays of the Higgs boson to a pair of light pseudoscalar particles a(1) is performed under the hypothesis that one of the pseudoscalars decays to a pair of opposite sign muons and the other decays to b (b) over bar. Such signatures are predicted in a number of extensions of the standard model (SM), including next-to-minimal supersymmetry and two-Higgs-doublet models with an additional scalar singlet. The results are based on a data set of proton-proton collisions corresponding to an integrated luminosity of 35.9 fb(-1), accumulated with the CMS experiment at the CERN LHC in 2016 at a centre-of-mass energy of 13 TeV. No statistically significant excess is observed with respect to the SM backgrounds in the search region for pseudoscalar masses from 20 GeV to half of the Higgs boson mass. Upper limits at 95% confidence level are set on the product of the production cross section and branching fraction, sigma B-h(h -> a(1)a(1) -> mu (+)mu(-) b (b) over bar), ranging from 5 to 33 fb, depending on the pseudoscalar mass. Corresponding limits on the branching fraction, assuming the SM prediction for sigma(h), are (1-7) x 10(-4). (C) 2019 The Author(s). Published by Elsevier B.V.